Qualidade da carcaça e da carne de bovinos nelore em diferentes intensidades de pastejo de capim xaraés - Silva, Bruno Lala (2015)
The objective was to assess whether the grazing height modifies the characteristics of carcass and meat, qualitatively and quantitatively, of 72 Nellore cattle submitted to different grazing heights (15, 30, 45 and 60 cm) of Brachiaria brizantha cv. Xaraes (xaraes grass) for two years, starting in November 2011 and finishing in June 2013. The experiment was lead in Cidade Gaucha City, Parana, Brazil South, at Farm 46, in a pasture previously fertilized with poultry manure and urea. Animals were kept in paddocks of 1 hectare with grazing under continuous variable stocking, in a completely randomized design with three pickets at each height, and three animals in each paddock (beyond the height regulators animals), totaling 9 replicates per treatment. Twenty-four hours after slaughter qualitative and quantitative analyzes of the carcass and the animal meat (using the Longissimus muscle) were performed and the influence was due to change in the experimental years for the following variables: leg thickness (24.89 cm year I, 23.98 cm year II), leg length (91.46 cm year I, 88.14 cm year II), carcass length (129.64 cm year I, 121.83 cm year II), degree of finishing (lower value 2.75, year I, 60 cm), conformation (3.17 points year I, 2.83 points year II), fat thickness (4.19 mm year I, II year 3.21mm), fat percentage (23.77% year I, II 26.53 years), bone percentage (16.74% year I, 19.85% year II), muscle percentage (60.13% year I, 53.63% year II), pH (5.94 year I, II 5.77 year), lightness (L*, 33.32 years I, II year 35.46 ), redness (a*, 12:42 year I, II year 16:18), yellowness (b*, 8:13 year I, II 8.86 year), chroma (C*, 14.81 year I, 18:46, year II) and hue (h°, 33.34 years I, II 28.70 years). There were also changes in the profile of the fatty acids: lauric acid (minimum point 12.34% at 35.40 cm), conjugated linoleic acid (12.13% at 37.6 cm height), myristic acid (negative linear effect), eicosadienoic acid (minimum point 1.39% at 30.90 cm) heptadecenoic acid(lowest value of 0.85%, 30 cm) and oleic acid (greater value 39.71%, 30 cm) were notsimilar between the grazing heights. Percentage of omega-3 (n-3) and omega-6 (n-6) were higher and best at 30 cm grazing, with values of 2.61% and 8.32%, respectively. The production of grazing cattle based on the management of grazing heights incontinuous system offers additional advantages, considering that this usage is interesting to minimize production costs, greater stability of production, reducing dependence on external factors, increased use of natural conditions of climate and soil, what promotes a sustainable production system. The management of grazing height between 30 and 45 cm modifies the carcass of Nellore cattle at Longissimus muscle and improves the fatty acid levels relevant to human health, such as acids: lauric, conjugated linoleic, myristic, eicosadienoic, heptadecenoic and oleic, beyond the levels of n-3 and n-6.